Fucoxanthin production of microalgae under different culture factors: a systematic review - Khaw, Yam Sim; Md Yusoff, Fatimah; Tan, Hui Teng; Noor Mazli, Nur Amirah Izyan; Nazarudin, Muhammad Farhan; Shaharuddin, Noor Azmi; Omar, Abdul Rahman; Takahashi, Kazutaka (Multidisciplinary Digital Publishing Institute, 2022)
Fucoxanthin is one of the light-harvesting pigments in brown microalgae, which is increasingly gaining attention due to its numerous health-promoting properties. Currently, the production of microalgal fucoxanthin is not yet feasible from an economic perspective. However, the cultivation of microalgae at favourable conditions holds great potential to increase the viability of this fucoxanthin source. Hence, this study aimed to review the fucoxanthin production of microalgae under different conditions systematically. A literature search was performed using the Web of Science, Scopus and PubMed databases. A total of 188 articles were downloaded and 28 articles were selected for the current review by two independent authors. Microalgae appeared to be a more reliable fucoxanthin source compared to macroalgae. Overall, a consensus fucoxanthin production condition was obtained and proposed: light intensity ranging from 10 to 100 µmol/m2/s could achieve a higher fucoxanthin content. However, the optimal light condition in producing fucoxanthin is species-specific. The current review serves as an antecedent by offering insights into the fucoxanthin-producing microalgae response to different culture factors via a systematic analysis. With the current findings and recommendations, the feasibility of producing fucoxanthin commercially could be enhanced and possibly achieve practical and sustainable fucoxanthin production.